Effect of Conceptual Understanding Procedures (Cups) Model on Mathematics Learning Results on SPLDV Materials - Tarashifa, Putri Salwa; Wantika, Restu Ria (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
Improving student learning outcomes in mathematics is not only done through memorization of material, but also requires an understanding of concepts and problems so that laters student are able to solve problems. In overcoming these problems, the CUPs (Conceptual Understanding Procedures) model is needed as an innovative learning model to provide an increase in student learning outcomes. Providing a description of the effect of student learning outcomes through the application of CUPs (Conceptual Understanding Procedures) is the purpose of this study. Including quantitative research, with Pre-test Ppost-test Non-Equivalent Control Group Design. Class VIII SMP Negeri 12 Surabaya os the population in this study with respondents, namely students of class VIII-F as the experimental class and VIII-G as the control class, each totaling 32 students. Data collected through questions that have been fulfilled through analyzing. The analysis that underlies the acquisition which is and . Because in the sense that the teaching results experience differences in the experimental class after going through the application of CUPs (Conceptual Understanding Procedures) and control through conventional models. So it is concluded that teacing with CUPs (Conceptual Understanding Procedures) has an influence on the learning outcomes of junior high scholl mathematics students.